2005
DOI: 10.1017/s0014479705002668
|View full text |Cite
|
Sign up to set email alerts
|

Field Evaluation of Root Rot Disease and Relationship Between Disease Severity and Yield in Cassava

Abstract: Reports of cassava root rot disease from different African countries have increased in recent times. Field studies were conducted from July 1998 to October 1999 to determine a reproducible disease assessment method that would allow the comparison of results from different locations and an evaluation of the relationship between disease severity and root yield. Single point disease assessments at 6, 9, 12 and 15 months after planting (MAP) were compared to multiple points assessment based on the area under a dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 8 publications
2
21
0
2
Order By: Relevance
“…However, the finding that none of the farmers had unharvested cassava from previous year at the time of this survey suggests that the intensity of the practice is low. Root rot (Onyeka et al, 2005) and lignification were reasons why farmers do not leave cassava roots unharvested for long periods after maturation. Thus there are limitations to the practice of delay harvesting of cassava.…”
Section: Discussionmentioning
confidence: 99%
“…However, the finding that none of the farmers had unharvested cassava from previous year at the time of this survey suggests that the intensity of the practice is low. Root rot (Onyeka et al, 2005) and lignification were reasons why farmers do not leave cassava roots unharvested for long periods after maturation. Thus there are limitations to the practice of delay harvesting of cassava.…”
Section: Discussionmentioning
confidence: 99%
“…Cassava roots (traditional varieties) can be stored in the ground for up to 24 months, and some varieties for up to 36 months. Harvest may be delayed until market, processing, or other conditions are favourable (Onyeka et al, 2005). These attributes make cassava an important food security crop in Nigeria and several other sub-Saharan African countries that produce the crop.…”
Section: Introductionmentioning
confidence: 99%
“…The resistance reference (30572) was classified as moderately resistant in this study, this genotype however, showed a good level of field resistance to root rot disease in our previous study (Onyeka et al, 2005a). The performance of 30572 necessitates the need for a classification method that is independent of the control for separation of the genotypes into levels of resistance.…”
Section: Discussionmentioning
confidence: 69%
“…There have been efforts to characterise some of the African landraces and breeders' lines for resistance to other diseases of cassava (Fokunang et al, 2000), but the distribution of resistance to root rot disease in these collections remains unknown. Variations in the response of different cassava genotypes to root rot disease have been demonstrated in field studies (Onyeka et al, 2005a). However, the long growth cycle for cassava to develop storage roots for assessment and the nonuniform distribution of inoculum in the soil make field screening very difficult.…”
Section: Introductionmentioning
confidence: 99%